2009
DOI: 10.1111/j.1750-3639.2008.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 7q34 in Pediatric Low‐Grade Astrocytomas Detected by High‐Density Single‐Nucleotide Polymorphism‐Based Genotype Arrays Results in a Novel BRAF Fusion Gene

Abstract: In the present study, DNA from 28 pediatric low-grade astrocytomas was analyzed using Illumina HumanHap550K single-nucleotide polymorphism oligonucleotide arrays. A novel duplication in chromosome band 7q34 was identified in 17 of 22 juvenile pilocytic astrocytomas and three of six fibrillary astrocytomas. The 7q34 duplication spans 2.6 Mb of genomic sequence and contains approximately 20 genes, including two candidate tumor genes, HIPK2 and BRAF. There were no abnormalities in HIPK2, and analysis of two mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
220
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(235 citation statements)
references
References 33 publications
11
220
3
1
Order By: Relevance
“…We identify additional genetic regions in JPA without 7q34 duplication ( Table 3) and show that most genes within these regions are modulators of the immune system. Specificity of 7q34 duplication to JPA and its prevalence in infratentorial tumours contrast with previous reports alluding that 7q34 duplication may be present in non-JPA LGA (Deshmukh et al, 2008;Pfister et al, 2008;Sievert et al, 2008) and is more frequent in non-cerebellar LGA (Pfister et al, 2008;Sievert et al, 2008). Deshmukh et al showed 7q34 duplication in 8 of 10 cerebellar JPA and further used increased HIPK2 expression on tissue microarray as a surrogate for marker for this genetic event.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…We identify additional genetic regions in JPA without 7q34 duplication ( Table 3) and show that most genes within these regions are modulators of the immune system. Specificity of 7q34 duplication to JPA and its prevalence in infratentorial tumours contrast with previous reports alluding that 7q34 duplication may be present in non-JPA LGA (Deshmukh et al, 2008;Pfister et al, 2008;Sievert et al, 2008) and is more frequent in non-cerebellar LGA (Pfister et al, 2008;Sievert et al, 2008). Deshmukh et al showed 7q34 duplication in 8 of 10 cerebellar JPA and further used increased HIPK2 expression on tissue microarray as a surrogate for marker for this genetic event.…”
Section: Discussionmentioning
confidence: 38%
“…They also show that one sample was classified as a grade II astocytoma; however, the child had prolonged disease-free survival more in keeping with a diagnosis of JPA. This misclassification might also account for the findings of 7q34 duplication in some non-JPA LGA in the study by the other groups (Deshmukh et al, 2008;Pfister et al, 2008;Sievert et al, 2008). The central review of samples by senior paediatric neuropathologists we performed has been shown to increase reproducibility of neuropathologic classification of tumours (Pollack et al, 2003) and may account for increased accuracy in our dataset.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…[8][9][10][11][12][13] The biologic significance of BRAF duplication lies in the activation of the MAPK pathway, which can drive tumor proliferation. 9 In addition to KIAA1549:BRAF fusion product, other molecular alterations have been reported in pilocytic astrocytoma, including other BRAF fusion products, 14,15 rare BRAF V600E mutations, 16 BRAF insertions, 17 and KRAS mutations.…”
mentioning
confidence: 99%